OPTIMIZATION OF TEACHER QUALITY CONTROL AT BAGAN BATU DEVELOPMENT COLLEGE FOUNDATION WITH E-MONEVA - Rizki Candra Dermawan; Evawany Yunita Aritonang; Meilita Tryana Sembiring (CV. RADJA PUBLIKA, 2025)
Technological advances enable human resource practices towards E-Human Resources. Monitoring and evaluation activities at Yayasan Perguruan Pembangunan Bagan Batu are carried out conventionally so that there are several problems, namely monitoring and evaluation activities are considered less effective and efficient, paper and printing costs and then problems in archiving. The aim is to create an E-Moneva design to optimize quality control activities at Yayasan Perguruan Pembangunan Bagan Batu. The method used is double diamond, the stages are discover, define, develop and delivery. The research results of respondents agreed that E-Moneva can optimize monitoring and evaluation activities by overcoming problems that exist in ongoing activities. E-Moneva can simplify the monitoring and evaluation process and help identify problems and assist in decision making. Monitoring and evaluation activities will run more effectively and efficiently because the features available on E-Moneva are able to support efforts to optimize teacher quality control. The principals agreed that E-Moneva could optimize monitoring and evaluation activities.